Horticulture Research Amidst Current Challenges in Northeast India - Malhotra, S K; Srivastava, A K (Indian Horticulture, 2024)
Horticulture in Northeast India has always been the torch bearer to science enthusiasts, considering the region popularly acclaimed as a hot-spot for many crops. Researchers have been intensively experimenting to ensure path-defining breakthroughs from various angles, however, with limited success due to stalemate research blue-prints adopted over the years for this region. The paper discusses the current challenges in research of the horticulture sector and the way out for the Northeast India.